To solve the equation -8x + 13 = -19, we can start by isolating the variable x.
First, we can subtract 13 from both sides of the equation:
-8x + 13 - 13 = -19 - 13
-8x = -32
Next, we can divide both sides of the equation by -8 to solve for x:
-8x / -8 = -32 / -8
x = 4
Therefore, the solution to the equation -8x + 13 = -19 is x = 4.
What is the solution of the equation -8x +13=-19
11 answers
4 or -4
I apologize, but the solution to the equation -8x + 13 = -19 is x = 4, not -4.
11- 4x =-9
To solve the equation 11 - 4x = -9, we can isolate the variable x.
First, we can subtract 11 from both sides of the equation:
11 - 4x - 11 = -9 - 11
-4x = -20
Next, we can divide both sides of the equation by -4 to solve for x:
-4x / -4 = -20 / -4
x = 5
Therefore, the solution to the equation 11 - 4x = -9 is x = 5.
First, we can subtract 11 from both sides of the equation:
11 - 4x - 11 = -9 - 11
-4x = -20
Next, we can divide both sides of the equation by -4 to solve for x:
-4x / -4 = -20 / -4
x = 5
Therefore, the solution to the equation 11 - 4x = -9 is x = 5.
just 5 or -5?
Apologies for the confusion. The solution to the equation 11 - 4x = -9 is x = 5, not -5.
2/5x + 3 = 1/5
To solve the equation 2/5x + 3 = 1/5, we can isolate the variable x.
First, we can subtract 3 from both sides of the equation:
2/5x + 3 - 3 = 1/5 - 3
2/5x = 1/5 - 15/5
2/5x = -14/5
Next, we can multiply both sides of the equation by the reciprocal of 2/5, which is 5/2, to solve for x:
(5/2)(2/5x) = (5/2)(-14/5)
x = -14/10
We can simplify -14/10 to -7/5, so the solution is x = -7/5.
First, we can subtract 3 from both sides of the equation:
2/5x + 3 - 3 = 1/5 - 3
2/5x = 1/5 - 15/5
2/5x = -14/5
Next, we can multiply both sides of the equation by the reciprocal of 2/5, which is 5/2, to solve for x:
(5/2)(2/5x) = (5/2)(-14/5)
x = -14/10
We can simplify -14/10 to -7/5, so the solution is x = -7/5.
im sorry i wrote it wrong, change the 4 to a 3
No problem! Let's solve the equation 2/5x + 3 = 1/5, with 3 instead of 4.
First, we can subtract 3 from both sides of the equation:
2/5x + 3 - 3 = 1/5 - 3
2/5x = 1/5 - 15/5
2/5x = -14/5
Next, we can multiply both sides of the equation by the reciprocal of 2/5, which is 5/2, to solve for x:
(5/2)(2/5x) = (5/2)(-14/5)
x = -14/10
We can simplify -14/10 to -7/5, so the solution is x = -7/5.
First, we can subtract 3 from both sides of the equation:
2/5x + 3 - 3 = 1/5 - 3
2/5x = 1/5 - 15/5
2/5x = -14/5
Next, we can multiply both sides of the equation by the reciprocal of 2/5, which is 5/2, to solve for x:
(5/2)(2/5x) = (5/2)(-14/5)
x = -14/10
We can simplify -14/10 to -7/5, so the solution is x = -7/5.